Sabah civil servants internet usage and its impact on their consumer behavior / Mohd Hamdan Haji Adnan, Mohd Adnan Hashim and Amir Shafiq. - Adnan, Mohd Hamdan; Hashim, Mohd Adnan; Shafiq, Amir (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2019)
From the end of the twentieth century to the early twenty first century the government of Malaysia is consistent in its efforts to make the information communication technology (ICT) usage as a way of life in the country. Promoting ICT usage as a way of life has been aggressively campaigned by the Federal Government since the Internet era began. It is expected that the civil servants should be among the first consumers to embrace ICT as compared to other citizens. This article researched Internet usage by Sabah civil servants and aims to discover whether it has impacted their consumer behaviour. The research used random sampling method with prepared questionnaires. It utilised the Uses and Gratifications Theory (UGT) to understand why and how the civil servants utilised the Internet to meet their needs. Altogether 12 Sabah government agencies comprising 316 respondents from the top to the lowest grades participated in this study. The findings revealed that Sabah civil servants nearly fully embrace the Internet and its impact on their consumer behaviour is significant. They are increasingly spending more time on the Internet via the social media to socialise, to enhance their knowledge, to buy online and to even try to earn extra income.